An Observational Study Investigating Potential Risk Factors and Economic Impact for Bovine Ischaemic Teat Necrosis on Dairy Farms in Great Britain - Crosby-Durrani, Hayley E.; Blowey, Roger W.; Manning, Al; Afonso, João Sucena; Carter, Stuart D.; Evans, Nicholas J.; Angell, Joseph W. (Frontiers in Veterinary Science, 2022)
Bovine ischaemic teat necrosis (ITN) is an emerging disease of unknown aetiology that affects the teats of dairy cattle. It causes economic and animal welfare issues with many animals being culled. No effective treatments or epidemiological data to inform control strategies are currently available. The aim of this observational study was to investigate farmer-reported experiences, and identify potential farm-level risk factors. In January 2018, a questionnaire was sent to a random sample of 1855 Great Britain (GB) dairy farmers. A usable response rate of 12.3% was obtained. Fifty-one percent (95% confidence interval (CI): 44.4 - 57.8%) of farmers reported having experienced ITN on their farm between 1985-2018. Rising numbers of farms indicated ITN is an emerging disease with 46.3% of farmers reporting the first case in the three years up to 2018. At the animal level, 47.3% (95% CI: 38.7-55.9%) of cases occurred during the first lactation and 78.9% (95% CI: 75.2-82.6%) within the first 90 days in milk. Only 20.8% (95% CI: 15.9-26.4%) of cases were reported to recover, whereas 22.8% (95% CI: 17.8-28.5%) of cases required culling. The remaining cases experienced complications such as loss of a teat and/or mastitis. From these data, the cost of ITN, through production losses and expenditure, was estimated to be £1121 per farm per year. The costs were estimated at £720, £860 and £2133 for recovered, complicated and culled cases, respectively. Univariable and multivariable logistic regression models were used to explore associations between the presence of ITN on farm and various risk factors. The presence of udder cleft dermatitis (UCD) (odds ratio 2.80; 95% CI: 1.54-5.07; p-value <0.01) and chapped teats (odds ratio 6.07; 95% CI: 1.96-18.76; p-value <0.01) in the milking herd were associated with the presence of ITN at farm-level. This is the first national questionnaire of ITN within GB and highlights the association of UCD and chapped teats with ITN at farm-level. While there are many limitations and potential bias around farmer questionnaires these findings highlight several key areas for further disease investigation and possible intervention.